Diagnosis challenges and accessibility barriers to migraine management in Southeast Asia: results from the South-East Asia Local breAch on MigraiNe Treatment (SEALANT) study - Rattanawong, Wanakorn; Hiransuthikul, Akarin; Anukoolwittaya, Prakit; Pongpitakmetha, Thanakit; Thanprasertsuk, Sekh; Manohararaj, Nijanth; Wan Sulaiman, Wan Aliaa; Saranza, Gerard; Wee, John Luis; Dayrit, Greg; Madjid, Irma Savitri; Sudibyo, Devi Ariani; et al. (BioMed Central, 2026)
Background: Migraine is one of the leading causes of disability among all neurological diseases, yet major gaps persist in diagnosis and access to effective treatment, particularly in low- and middle-income regions. Southeast Asia and East Asia are characterised by marked socioeconomic diversity, variable healthcare infrastructure, and limited availability of migraine-specific therapies. We aimed to assess physician-reported barriers to migraine diagnosis and management across Southeast Asian and East Asian countries. Methods: The South-East Asia Local breAch on MigraiNe Treatment (SEALANT) study was a multinational, cross-sectional, web-based survey conducted between Nov 1, 2024, and Aug 31, 2025. Physicians involved in migraine care from Laos, Indonesia, Malaysia, the Philippines, Singapore, Taiwan, and Thailand were eligible. Survey domains included diagnostic barriers, clinic accessibility, acute and preventive treatment practices, awareness of medication overuse headache, access to calcitonin gene-related peptide (CGRP)–targeted therapies, and migraine-related stigma. Countries were categorised by World Bank income classification. Data were analysed descriptively, and comparisons were made across income groups. All results are based on physicians’ perceptions of routine clinical practice rather than objectively verified patient-level data. Results: A total of 686 physicians participated (mean age 39.0 years [SD 9.9]), of whom 79.8% were neurologists. Overall, 70.0% of respondents reported an insufficient number of neurology/headache clinics, increasing to 87.2% in lower-middle-income countries. Physicians reported that approximately 60.0% of patients were correctly diagnosed with migraine before specialist consultation, while 44.9% were perceived to experience diagnostic delays exceeding one year. According to physician reports, acute migraine management relied predominantly on non-specific analgesics, with opioids remaining widely available and prescribed across all income settings. Reported use of migraine-specific acute therapies and preventive treatments was limited. Although CGRP-targeted preventive therapies were widely regarded by physicians as effective (77.1%), many perceived that these treatments should not yet be reimbursed. Conclusion: Substantial and inequitable gaps persist in migraine diagnosis and management across Southeast Asia and East Asia, as perceived by physicians, driven by shortages of specialist services, delayed diagnosis, reliance on non-specific treatments, and restricted access to migraine-specific therapies. Addressing migraine as a public health priority through health-system strengthening, education, and equitable access to evidence-based treatments is essential to reduce disability in the region.